ANALISIS DAMPAK OPTIMASI SIMPANG BERSINYAL TERHADAP EMISI GAS BUANG - Kresna Raditya; Muhammad Rudissalam; Ismiyati Ismiyati; Kami Hari Basuki (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Siliwangi road is one soars and populous Primary Arterial Road in the Semarang City, so often there is congestion on the roads. Result of frequent congestion on the roads, air pollution which occurs also higher. This study aims to determine how high the air pollution that occur and to provide recommendations for alternative solutions to tackle congestion at the intersection whole observatories, so as to minimize the air pollution that occurs. Traffic survey at the intersection whole observatories done during the morning Peak hour, afternoon Peak hour and evening Peak hours. Survey results are then processed by the Manual Kapasitas Jalan Indonesia (MKJI) 1997 Synchro SimTraffic Program 7.0. Initially, the green time adapted to the needs of the existing condition, then the following adjustments were made in the form of changes in the geometric intersection to accommodate existing traffic conditions. Adjustment of the traffic conditions and the geometric path then known how much pollution that occurred at the intersection. At the intersection of the existing conditions in whole observatories already reached saturation performance , with the calculation of the degree of saturation of the synchro program 7 that almost all of them are above the 1.00 figure. With the adjustment Optimization green time to Simpang whole observatories provide DS to decrease Morning Peak condition that is equal to 5.82%, 5.82% Peak Afternoon, Evening Peak 9.89% and the change in geometric intersection (lane additions of 3.7 m) on condition Morning Peak, Peak Afternoon, Evening Peak resulting decrease in DS respectively 23.80%, 8.95%, and 14.58%. Although not all perform well and there are still some poor performers approach (indicators of poor performance where the value of the degree of saturation exceeds the ideal value of the degree of saturation (DS>0.75). Use of Public Transport assuming 50% removal of the car was replaced with highly efficient use of BRT in reducing the number of DS on condition Morning Peak , Peak Lunch, Afternoon Peak resulting decrease in DS respectively 60.84%, 47.01%, and 61.97%. The scenario design is done well enough for the level of handling performance in the short term. So, it can be concluded that the performance of intersections that were reviewed for the better.